2019
DOI: 10.1098/rstb.2018.0117
|View full text |Cite
|
Sign up to set email alerts
|

The development of individual differences in cooperative behaviour: maternal glucocorticoid hormones alter helping behaviour of offspring in wild meerkats

Abstract: One contribution of 18 to a theme issue 'Developing differences: early-life effects and evolutionary medicine'.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…We included a two-way interaction term between treatment and litter size to identify whether elevations in maternal GCs altered the trade-off between litter size and offspring birth mass, growth or size, as shown previously for offspring growth (Dantzer et al, 2013). We included a two-way interaction between treatment and sex to assess whether the treatments had sex-specific effects on birth mass, growth and size, as documented in other species (Dantzer et al, 2019). In our model for the effects of the treatments on offspring birth mass, we included a fixed effect for age of the pups to control for the impact of age on body mass.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…We included a two-way interaction term between treatment and litter size to identify whether elevations in maternal GCs altered the trade-off between litter size and offspring birth mass, growth or size, as shown previously for offspring growth (Dantzer et al, 2013). We included a two-way interaction between treatment and sex to assess whether the treatments had sex-specific effects on birth mass, growth and size, as documented in other species (Dantzer et al, 2019). In our model for the effects of the treatments on offspring birth mass, we included a fixed effect for age of the pups to control for the impact of age on body mass.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Studies of two other avian species, western bluebirds (Sialia mexicana) and great tits (Parus major), found an effect of maternal androgen deposition on offspring dispersal in response to ecological conditions (Duckworth, 2009;Tschirren et al, 2007). Viviparous lizards (Lacerta vivipara) show a similar effect (Meylan et al, 2002), and maternal hormones have also been shown to increase helping behavior in subordinate female meerkats (Suricata suricatta) (Dantzer et al, 2019). Further work in this and other cooperatively breeding species should examine the mechanism by which environmentally-mediated parental effects might influence future reproductive tactics adopted by offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Male superb starlings are more likely to become alloparents and help more than females (Rubenstein, 2011), and alloparents buffer the detrimental effects of harsh environmental conditions on reproductive success in this species (Guindre-Parker and Rubenstein, 2018). Thus, prenatal parental effects promoting alloparental behavior following harsher prenatal conditions might serve to selfishly increase the parents' short-term future reproductive success and indirectly limit dispersal of male offspring (Dantzer et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They offer a way to measure the fitness impacts of variation in early life conditions, and test evolutionary hypotheses about the causes and consequences of developmental responses. Dantzer et al [52] show that a manipulation of early-life maternal hormone exposure affects later-life cooperative behaviour in a female, but not male, meerkats (Suricatta suricatta). Their findings suggest that these earlylife effects may be in the interests of parents, but not offspring.…”
Section: Overview Of the Issuementioning
confidence: 99%